Atividade lítica pelo sistema complemento em promastigotas de Leishmania (Leishmania) infantum frente a componentes salivares de Lutzomyia (Lutzomyia) longipalpis (Diptera: Psychodidae) - Alexandre Alves de Sousa Nascimento (2011)
Since the first reports about visceral leishmaniasis in Brazil, the sand fly Lutzomyia longipalpis has been incriminated as the main vector of Leishmania infantum, the causative agent of visceral leishmaniasis in the Americas. The saliva of the vector modulates the host immune response at different levels, including inhibition of the complement activation, making it a critically important component in the process of disease transmission. This study aimed to show the importance of salivary inhibitors of the complement of L. longipalpis for the survival of L. infantum promastigotes when exposed to both, human and dog serum. The amount of saliva released by females in the byte site during blood feeding was also estimated. Considering that opsonization with C3b seems important for Leishmania phagocytosis in a manner that avoid macrophages activation, we investigated the deposition of C3b on the parasite surface in the presence or absence of saliva by indirect immunofluorescence. Stationary phase promastigotes were partially sensitive to the normal human serum (5% of serum killed almost 50% of the promastigotes). We observed a significant reduction of cell death when promastigotes were exposed to the normal human serum in the presence of saliva. This effect was dependent of saliva concentration. Despite showing partial sensitivity to human complement, promastigotes presented great resistance to lysis by complement of infected dogs and uninfected ones. For all hosts, C3b deposition was efficient in the presence and absence of saliva, showing that, while diminishing the lytic action by normal human serum, saliva does not prevent the promastigote opsonization by complement. Since saliva favors the survival of L. infantum promastigotes when exposed to the human serum, it could be critical in the process of transmitting the parasite to the man. Altogether, our results could explain why dogs are more susceptible to be infected by L. infantum than humans